Consumer Misuse of Cosmeceuticals and Its Role in Adverse Skin Reactions - Suraj Sen; Anit Jha; Praveen Yadav; Shah Mohmmed; Vikash Prajapati; Ajay Kumar (International Journal of Toxins and Toxics, 2026)
Cosmeceuticals represent a rapidly expanding category of products positioned between cosmetics and pharmaceuticals, offering both aesthetic and therapeutic benefits. However, their widespread availability, aggressive marketing, and perception as inherently safe have contributed to increasing instances of consumer misuse. Misuse includes over-application, inappropriate combinations, prolonged unsupervised use, and use of high-potency active ingredients without dermatological guidance. Such practices have been strongly associated with a broad spectrum of adverse cutaneous reactions ranging from mild irritation to severe dermatological conditions such as steroid-induced dermatitis, exogenous ochronosis, and contact dermatitis. Recent literature highlights that commonly used ingredients such as hydroquinone, retinoids, alpha-hydroxy acids (AHAs), and topical corticosteroids are frequently implicated in adverse outcomes when misused. The growing trend of self-medication, especially in skin-lightening and anti-aging regimens, exacerbates the risk. Furthermore, sociocultural influences, including beauty standards and digital media promotion, play a significant role in shaping unsafe consumer behavior. This review critically examines patterns of cosmeceutical misuse, identifies high-risk ingredients, and explores the mechanisms underlying adverse skin reactions. It also discusses regulatory challenges and proposes preventive strategies aimed at improving consumer awareness and dermatological safety. Understanding these factors is essential for healthcare professionals, pharmacists, and regulatory authorities to mitigate risks and promote rational cosmeceutical use.
Keywords: Adverse Skin Reactions; Cosmeceuticals; Cosmetovigilance; Dermatotoxicity; Hydroquinone; Misuse; Retinoids; Skin Irritation; Topical Steroids; consumer behavior